Implementation of the Full Day School Program in Improving Student Character at the Darul Ulum Bumbungan Bluto Sumenep Integrated Elementary School in 2024 - Mery Hidayati; Abdul Qodir Jailani (Penerbit Hellow Pustaka, 2025)
Full day school is a learning system that is implemented fully, where children's activities are mostly carried out at school rather than at home. The Darul Ulum Integrated Elementary School has a special challenge, namely character formation in students. To find out more about the implementation of the full day school program in improving student character education and to answer the focus of the research, the researcher used a descriptive qualitative approach and used a phenomenological research type and used the interview, observation and documentation research methods. From the method, the researcher processed and analyzed data to obtain data or information. The subjects of this study were taken from 3 (three) school stakeholders, 3 (three) students and 2 (two) parents of students and literature searches for data related to books and journals for validity, researchers can use triangulation with source triangulation. The results of this study are the implementation of the full day school program in improving student character: Cognitive spirit, Affective spirit, Psychomotor spirit and spiritual aspects. The impact of implementing the full day school program is divided into two, namely positive impacts, namely: optimizing the use of time, children are well controlled, there is an emotional relationship between teachers and students, there is a positive response from parents of students. Negative impacts, namely: lack of interaction with family, boredom and fatigue, minimal freedom.